2012
DOI: 10.1152/ajprenal.00134.2012
|View full text |Cite
|
Sign up to set email alerts
|

Human SLC2A9a and SLC2A9b isoforms mediate electrogenic transport of urate with different characteristics in the presence of hexoses

Abstract: Human SLC2A9 (GLUT9) is a novel high-capacity urate transporter belonging to the facilitated glucose transporter family. In the present study, heterologous expression in Xenopus oocytes has allowed us to undertake an in-depth radiotracer flux and electrophysiological study of urate transport mediated by both isoforms of SLC2A9 (a and b). Addition of urate to SLC2A9-producing oocytes generated outward currents, indicating electrogenic transport. Urate transport by SLC2A9 was voltage dependent and independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…Detailed characterization of hSLC2A9 indicates that this transporter exhibits hexose/hexose transacceleration and hexose/urate exchange across the cell membrane (13,14). That is, hexose on one side of the membrane can stimulate the unidirectional flow of hexose or urate from the other side of the membrane.…”
mentioning
confidence: 99%
“…Detailed characterization of hSLC2A9 indicates that this transporter exhibits hexose/hexose transacceleration and hexose/urate exchange across the cell membrane (13,14). That is, hexose on one side of the membrane can stimulate the unidirectional flow of hexose or urate from the other side of the membrane.…”
mentioning
confidence: 99%
“…It is a causative gene for renal hypouricemia and plays a key role in urate reabsorption by renal proximal tubular cells (Preitner et al, 2009). Recently, studies have reported that SLC2A9 plays a crucial role in the incidence of gout (Tin et al, 2011;Witkowska et al, 2012). Another study showed that rs13129697, located in intron 7 of SLC2A9, showed the strongest association with gout (Karns et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most significant findings include single nucleotide polymorphisms (SNPs) located within the SLC2A9 gene and the intergenic region between SLC2A9 and ZNF518B on chromosome 4 (Döring et al, 2008). SLC2A9 encodes the GLUT9 renal molecule, which transports glucose and later transports uric acid (Caulfield et al, 2008;Witkowska et al, 2012). ZNF518B is a novel gene that has been identified to be associated with gout (Döring et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other members of the SLC2 family, GLUT9 has been shown to transport glucose and other sugars, although this has recently been questioned [21]. However, sugars may influence the transport of urate by GLUT9 [22], suggesting that dietary sugars can influence sUA levels through GLUT9. A short isoform of GLUT9 (GLUT9b or -S) differs at the amino terminus from the longer isoform due to alternative splicing.…”
Section: Glut9mentioning
confidence: 99%